Tele-mentorship versus in-person mentorship for trainee performance of cricothyroidotomy. - Rosenberg, Meagan L.; Goebel, Mathew; LaPorte, Mackenzie; Carpenter, Cassidy; Clark, Ryan; Kelly, Seth; Carey, Yamuna; Kelly, Edward; Kamine, Tovy H. (Trauma, 2025)
Introduction: Physicians and other first-line medical care providers may find themselves in an airway management emergency where they cannot ventilate, cannot oxygenate, and have limited resources to aid them. The rise in use of tele-health and other virtual interfaces creates the opportunity to bring experienced guidance to a resource-poor critical airway situation. We aimed to compare in-person mentoring (IPM) by an emergency medicine (EM) physician to tele-mentoring (TM) by a trauma surgeon for an emergent surgical airway. Methods: Thirty EM residents were randomized to cricothyroidotomy on a model with IPM or TM. The IPM preceptor was an EM attending, and TM preceptors were trauma surgeons. The procedure was timed and graded on a Global Rating Scale (GRS). Post-procedure, mentor and trainee completed a NASA Task Load Index (TLX). Results: There was no difference in procedure success; however, the IPM group took longer (163.6 vs. 107.6 s, p < 0.05). TM trainees experienced greater temporal demand (4.27 vs. 2.73, p = 0.03). Telementors recorded improved performance compared to in-person mentors (2.30 vs. 4.17, p < 0.05). Comparing mentors and trainees in each arm, IPM trainees felt more temporal demand than their mentors (4.63 vs. 2.73, p < 0.05) while TM trainees felt they had worse performance than their mentors perceived (4.23 vs. 2.3, p = 0.01). Discussion: Performance based on GRS between groups was equal; however, those with telementors secured the airway more rapidly. Telementors reported higher performance and lower time pressure than in-person preceptors. This data suggests that TM is effective for precepting cricothyroidotomy and may be the superior option in some settings.